A CRITICAL ANALYSIS OF DHATUPAKA LAKSHANA WSR TO MADHUMEHA - DR. SUNIL KUMAR N; DR. SUNIL RAMACHANDRA KHANDARE (The Bioscan, 2025)
Ayurvedic physician’s even now diagnosing diabetes with the help of modern parameters such as laboratory findings of blood sugar levels FBS, PPBS, HbA1c etc. According to bruhatrayees and lagutrayees, prameha is divided into 20 types among them one is Madhumeha (Diabetes Mellitus). All these pramehas diagnosing with the help of Gandha, Varna, Rasa, Sparsha of mutra. Nowhere in classics, told about the exact or accurate lakshanas/symptoms of prameha.Majority of the aurvedic physicians are diagnosing prameha with the help of poorvarupa lakshanas such as malas accumulated in the dantha prathesha, pani-daha, pada-daha, trishna, excessive sweda, madhuryam-asyata. Dhatupaka is one among the least explained concepts in Ayurveda. But this state is closely related to the patho-physiology of multiple systemic disorders.